Women's volleyball team huddle - Anderson, Eric (Tufts Archival Research Center, 2014)
This date is approximate. 5 x 7 in., photographic print. Back of print reads: "W. volleyball; #2 Dana Cohen; #5 Jessica Stewart; 88% 7a; by Eric Anderson"